Impact Mechanism Of Chengdu Female Purchase Intention Of Cosmetic Products Under The Perceived Value Of Self-Improvement Of Domestic Products - Lingling Zhong (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Brand satisfaction and loyalty are critical aspects of management that help retain the market's competitive advantages. In the context of the self-improvement of domestic products, this study studies the influence mechanism of domestic cosmetics on purchase intention in Chengdu from the perspective of consumers' perceived value. It tests the research hypotheses through questionnaire surveys and practical analysis. It guides how local Chinese cosmetics companies can improve consumers' rational suggestions to perceive value and increase their purchase intention. The number of respondents for this study was 392. The results of this study highlight the significant role of female consumers in the purchase intention of domestic cosmetic products, which is influenced by their brand satisfaction and brand loyalty